Environmental DNA Time Series in Ecology. (December 2018) - Bálint, Miklós; Pfenninger, Markus; Grossart, Hans-Peter; Taberlet, Pierre; Vellend, Mark; Leibold, Mathew A.; Englund, Göran; Bowler, Diana
Abstract : Ecological communities change in time and space, but long-term dynamics at the century-to-millennia scale are poorly documented due to lack of relevant data sets. Nevertheless, understanding long-term dynamics is important for explaining present-day biodiversity patterns and placing conservation goals in a historical context. Here, we use recent examples and new perspectives to highlight how environmental DNA (eDNA) is starting to provide a powerful new source of temporal data for research questions that have so far been overlooked, by helping to resolve the ecological dynamics of populations, communities, and ecosystems over hundreds to thousands of years. We give examples of hypotheses that may be addressed by temporal eDNA biodiversity data, discuss possible research directions, and outline related challenges. Highlights: eDNA fills an important data gap for temporal ecology: it provides data over long time periods with high taxonomic breadth, permitting tests of hypotheses and models of biodiversity. Dynamic biodiversity data obtained with eDNA have the potential to reveal the long-term dynamics of populations, species, communities, and ecosystems in changing environments. eDNA records both ecological and evolutionary changes and thus may be used to understand eco-evolutionary feedbacks. Models of how historical environmental changes impact biodiversity may be hindcast validated with eDNA. Important challenges remain concerning the deposition and preservation of eDNA, the nature of different eDNA archives, and the interpretation of the resulting biodiversity data.